Are patients with stage III non-small cell lung cancer treated with chemoradiotherapy at risk for cardiac events? Results from a retrospective cohort study - Juliette Degens; D De Ruysscher; Ruud Houben; Bastiaan Kietselaer; Gerben Bootsma; Lizza Hendriks; Ellen Huijbers; Annemie Schols; Anne-Marie C Dingemans (BMJ Open)
Objectives Dyspnoea is one of the symptoms frequently encountered after treatment with chemoradiotherapy (CRT) in stage III non-small cell lung cancer (NSCLC). Long-term data on mild to moderately severe cardiac events as underlying cause of dyspnoea in patients with stage III NSCLC are lacking. Therefore, the incidence of new cardiac events, with a common terminology criteria for adverse events (CTCAE) score of ≥2 within 5 years after diagnosis, were analysed.Design Retrospective multicentre cohort study of patients with stage III NSCLC treated with CRT from 2006 to 2013. The medical files of the treated patients were reviewed.Outcome measures The primary endpoint of the study was the incidence of new cardiac events with a CTCAE score of ≥2 within 5 years after diagnosis. Secondary endpoint was to identify risk factors associated with the development of a cardiac event.Results Four hundred and sixty patients were included in the study. Of all patients, 150 (32.6%) developed a new cardiac event. In patients with a known cardiac history (n=138), 44.2% developed an event. The most common cardiac events were arrhythmia (14.6%), heart failure (7.6%) and symptomatic coronary artery disease (6.8%). Pre-existent cardiac comorbidity (HR 1.96; p<0.01) and WHO-performance score ≥2 (HR 2.71; p<0.01) were significantly associated with developing a cardiac event. The majority of patients did not have pre-existent cardiac comorbidity (n=322). Elevated WHO/International Society of Hypertension score was not identified as a significant predictor for cardiac events.Conclusion One-third of patients with stage III NSCLC treated in daily clinical practice develop a new cardiac event within 5 years after CRT. All physicians confronted with patients with NSCLC should take cardiac comorbidity as a serious possible explanation for dyspnoea after treatment with CRT.